Photodynamic therapy in patients with early central lung cancer - V. V. Sokolov; E. V. Filonenko (Biomedical Photonics)
The results of photodynamic therapy (PDT) for early central lung cancer are represented in the article. The study included 37 patients (52 tumor lesions). For 52 lesions pre-invasive cancer (carcinoma in situ) was determined in 6 cases, squamous cell cancer with invasion within mucosal and submucosal layers of bronchial wall – in 46 cases. 51 tumors were primary lesion, 1 – residual after radiotherapy. 17 of 37 patients underwent previous surgical or combined modality treatment for cancer in other anatomical sites. For PDT we used photosensitizers photogem, photosens and radachlorine. The treatment response was assessed 1 months later by data of endoscopy and morphological study, CT, US and endosonography. Complete regression was achieved in 86,5% of cases, partial regression – in 13,5%. The efficacy of PDT was depended on tumor size. For lesion up to 1 cm in size complete regression was in 100% of cases, from 1.5 cm to 2.0 cm – in 28.6%, for tumors more than 2 cm the complete regression was not achieved. The recurrence of tumor was diagnosed in 2 patients in the period from 1 to 5 years with following successful repeated courses of PDT. Adverse effects included inflammation changes in mucosa at the PDT region with transient (up to 6-7 days) local fibrinous endobronchitis with obturation of segmental bronchial lumen by fibrin membranes (7 patients), scar stenosis of segmental bronchus (2 patients). All patients had increased sensitivity to sun exposure, mild skin burns at exposed areas of body were in 2 patients. The results showed that method was highly efficient and applicable for pre-invasive central lung cancer and in patients with multiple primary bronchial lesions and high risk of surgical complications.